ANALISIS PEMANFAATAN SISTEM INFORMASI PENDIDIKAN DALAM KOMUNIKASI SEKOLAH DAN ORANG TUA SISWA DI SDN 5 SELONG - Fahrun Fahrun; Husnul Mukti; Hadijah Hadijah (STKIP Pesisir Selatan, 2026)
With the advancement of information technology, schools are encouraged to use educational information systems as a medium of communication with parents. Effective communication is essential in helping schools and parents support students' learning success. The purpose of this study is to analyze the use of educational information systems in school-parent communication at SDN 5 Selong. This research includes the communication media, the type of information conveyed, the perceived benefits, and the obstacles faced. This study used a quantitative descriptive approach with a sample of 73 parents/guardians selected by the purposive sampling method. Data collection using Google Form questionnaires, interviews, and documentation. Descriptive analysis is used using frequency and percentage. The results showed that the most effective communication medium was WhatsApp Groups (86.3%). The most common information received by parents was about school activities (79.5%), student assignments (69.9%), and assessment schedules (64.4%). The main advantages felt were faster reception of information (84.9%) and ease of communication with teachers (75.3%). The biggest challenges are internet disruptions (38.4%) and limited data quotas (30.1%). The results of the study prove that educational information systems allow effective communication between schools and parents.